Feminism: A very short introduction - Walters, Margaret (Oxford University Press, 2005)
This text provides an historical account of feminism, exploring its earliest roots and key issues such as voting rights and the liberation of the sixties. Walters brings the subject completely up to date by providing a global analysis of the situation of women, from Europe and the United States to Third World countries.
Keywords: amériques; cours; discipline; droits des femmes*; europe; fem1000; histoire; histoire du féminisme; mouvements féministes; premier cycle; ressource en ligne; régions géographiques; sciences humaines; thématiques; états-unis